Chapter Le competenze digitali degli insegnanti - Ranieri, Maria (Strumenti per la didattica e la ricerca, 2022)
Over the last years, the interest in teachers' digital competence has become the object of increasing attention. The progressive digitalization of our societies led the European legislator, in 2006, to reformulate the framework of key competences, introducing digital competence among the new knowledge that school has to promote. Of course, both future and in-service teachers need to be prepared to favour students' digital skills. This brought the European Commission to release in 2017 the DigCompEdu framework. In this chapter, we will first review some of the main conceptual models inspiring the reflection and research around teachers' knowledge and digital skills. Then, we will focus on the DigComEdu framework, to illustrate its main areas of competences and the operational values.